Peran Mediasi Kepuasan Kerja dalam Hubungan antara Motivasi Kerja dan Kinerja Pegawai: Bukti dari Institusi Pemerintah - Rince Tambunan; Bakhtiar Abbas; Muh. Nur (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study investigates the influence of job satisfaction on employee performance, the impact of work motivation on job satisfaction, and the mediating role of job satisfaction in the relationship between motivation and performance among civil servants working at the Secretariat of the Regional House of Representatives (Dewan Perwakilan Rakyat Daerah, DPRD) of Konawe Regency, Indonesia. A total of 53 employees participated as respondents. Data were collected through questionnaires and in-depth interviews. The Partial Least Squares (PLS) method was used to test the hypotheses, complemented by qualitative analysis to deepen understanding of the findings. Results indicate a strong correlation between motivation, job satisfaction, and performance, suggesting that increased motivation and satisfaction lead to better employee outcomes. However, intrinsic motivation alone is insufficient; external support, such as effective managerial practices, is needed to enhance performance. The findings underscore the significant mediating role of job satisfaction in the link between motivation and performance. Based on these insights, the study recommends that the DPRD Secretariat and related government institutions adopt targeted interventions to improve employee engagement and performance.